A Generalised Plastic Model for Gravelly Soils Considering Evolution of Void Ratio and Particle Breakage - Zhang, Jiuchang; Li, Yue; Wang, Rubin (Frontiers in Physics, 2021)
Gravelly soils exhibit complicated mechanical behaviours closely related to particle breakage and relative density state. To better capture the mechanical responses of gravelly soils, a generalised plastic model considering evolution of void ratio and particle breakage was developed within the framework of critical state soil mechanics. In the model, particle breakage effect was described by incorporating breakage index to deviate the critical state line off the ideal position. A differential equation relating increment of void ratio to variation of volumetric strain was used to depict the evolution of current void ratio. It indirectly reflected the relative density state of gravelly soils. The model was applied to conducting numerical simulations for a series of triaxial tests on four types of gravelly soils. Comparisons between the test data and the modelling results indicated that considerations of void ratio evolution and particle breakage could better simulate the stress-dependent dilatation/contraction behaviours of gravelly soils.